Analisis Perbandingan Rute Distribusi Menggunakan Metode Saving Matrix Dan Nearest Neighbor Di Center Kantor Pos Mpc Bandung - Lusel, Rikardo Riki; Permadi, Dodi; Mulyati, Erna (Innovative: Journal Of Social Science Research, 2024)
PT Pos Indonesia (Persero) is a State-Owned Enterprise (BUMN) that provides postal mail, postal parcels, finance, logistics and agency services to the public. In distributing letters and packages PT Pos Indonesia uses 3 transportation, namely primary, secondary and tertiary transportation. The Bandung Post Processing Center in transporting letters and packages to the delivery center office uses tertiary transportation using 12 vehicles which causes a waste of cost, time and distance. This study aims to determine tertiary transportation routes from SPP Bandung to delivery centers that can minimize distribution costs, time and distance taking into account vehicle carrying capacity and demand in each delivery center. The method used is the saving matrixand the nearest neighbor to analyze and determine which of the two methods results in more savings and effectiveness in implementation. After that, it is compared with the current existing condition whether it is feasible to be used in activities in the company. The results of data processing show that using the nearest neighbor method can save a total mileage of 22.1%, a total distribution cost savings of 4.96% and a total savings of 15.67% travel time compared to using the saving matrix method.